Poverty and Globalization: the relationship and interaction (Journal of Economic Research & Business Administration, 2015)
The main symptoms and signs of poverty as a global socio-economic phenomenon in different countries. We investigated the relationship and interaction of the phenomenon of poverty and globalization.